Recommendations for perioperative management in the patient with COVID-19 - José Julio Ojeda González (Medisur)
Based on the elements offered by the World Health Organization, related to guidelines for the prevention and treatment of patients with COVID-19 and experiences of the medical personnel who care for these patients during the periperatory period, in addition to an updated literature review in this regard, recommendations are offered on the management of patients with COVID-19, during care by the anesthesiologist.